Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1117
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware Neural Machine Translation Learns Anaphora Resolution

Abstract: Standard machine translation systems process sentences in isolation and hence ignore extra-sentential information, even though extended context can both prevent mistakes in ambiguous cases and improve translation coherence. We introduce a context-aware neural machine translation model designed in such way that the flow of information from the extended context to the translation model can be controlled and analyzed. We experiment with an English-Russian subtitles dataset, and observe that much of what is captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
283
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(293 citation statements)
references
References 13 publications
9
283
1
Order By: Relevance
“…There are several works analyzing attention weights of different NMT models (Ghader and Monz, 2017;Voita et al, 2018;Raganato and Tiedemann, 2018). Raganato and Tiedemann (2018) use the self-attention weights of the Transformer's encoder to induce a tree structure for each sentence and compute the unlabeled attachment score of these trees.…”
Section: Related Workmentioning
confidence: 99%
“…There are several works analyzing attention weights of different NMT models (Ghader and Monz, 2017;Voita et al, 2018;Raganato and Tiedemann, 2018). Raganato and Tiedemann (2018) use the self-attention weights of the Transformer's encoder to induce a tree structure for each sentence and compute the unlabeled attachment score of these trees.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies revealed that inter-sentential context can implicitly help to tackle anaphora resolution in NMT architecture (Jean et al, 2017b;Bawden et al, 2018;Voita et al, 2018). Some may argue that document-level architectures are strong enough to alleviate ZP problems for NMT.…”
Section: Effect Of Discourse-level Contextmentioning
confidence: 99%
“…Though this problem has recently triggered a lot of attention to contextaware translation (Jean et al, 2017a;Wang et al, 2017;Tiedemann and Scherrer, 2017; Bawden 1 We release code and data sets at https://github.com/lena-voita/ good-translation-wrong-in-context. Voita et al, 2018;Maruf and Haffari, 2018;Agrawal et al, 2018;Miculicich et al, 2018;Zhang et al, 2018), the progress and widespread adoption of the new paradigm is hampered by several important problems. Firstly, it is highly non-trivial to design metrics which would reliably trace the progress and guide model design.…”
Section: Introductionmentioning
confidence: 99%